2022
DOI: 10.1021/acscatal.2c04158
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Pt Electrocatalysts via Introducing Reducible Oxide Support as Reservoir of Electrons and Oxygen Species

Abstract: The limited durability of Pt-based catalysts has largely plagued the road of proton conductive membrane fuel cell-based vehicles to the mass market for years. Herein, we overcome the degradation issue by employing intelligent catalyst design to concomitantly suppress the oxidation and dissolution of Pt via introducing reducible niobium oxide (Nb2O5) support as a reservoir for electron and oxygen species. Benefiting from the corrosion resistance of Nb2O5 and strong metal–support interactions, the Pt–Nb2O5 catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 43 publications
(87 reference statements)
1
16
0
Order By: Relevance
“…The calcination temperature-dependent study also shows similar results (Figure S20 and Table S5). Meanwhile, the peaks for Ir 4f all shift to lower binding energy compared to that of commercial IrO 2 (Figure S21), while in Ce 3d and O 1s XPS spectra, ho v -IrO x /CeO 2 and mo v -IrO x /CeO 2 all display a positive binding energy shift compared with Ce-BPyDC-derived CeO 2 and Ce-BPDC-derived CeO 2 , respectively (Figures S22 and S23), indicating electron flowing from CeO 2 to IrO x , which suggests a strong interaction between CeO 2 and IrO x in IrO x /CeO 2 catalysts . In addition, the signal resulting from the unpaired electrons could be provided by EPR measurements, which are affected by the density of oxygen vacancies in the materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calcination temperature-dependent study also shows similar results (Figure S20 and Table S5). Meanwhile, the peaks for Ir 4f all shift to lower binding energy compared to that of commercial IrO 2 (Figure S21), while in Ce 3d and O 1s XPS spectra, ho v -IrO x /CeO 2 and mo v -IrO x /CeO 2 all display a positive binding energy shift compared with Ce-BPyDC-derived CeO 2 and Ce-BPDC-derived CeO 2 , respectively (Figures S22 and S23), indicating electron flowing from CeO 2 to IrO x , which suggests a strong interaction between CeO 2 and IrO x in IrO x /CeO 2 catalysts . In addition, the signal resulting from the unpaired electrons could be provided by EPR measurements, which are affected by the density of oxygen vacancies in the materials.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, S23), indicating electron flowing from CeO 2 to IrO x , which suggests a strong interaction between CeO 2 and IrO x in IrO x /CeO 2 catalysts. 45 In addition, the signal resulting from the unpaired electrons could be provided by EPR measurements, which are affected by the density of oxygen vacancies in the materials. The profile for ho v -IrO x / CeO 2 shows a higher signal intensity than that of mo v -IrO x / CeO 2 and lo v -IrO x /CeO 2 , further indicating a significantly higher concentration of oxygen vacancies in ho v -IrO x /CeO 2 compared to the others (Figure 2d and Table S6).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Metal oxides (M = W, Nb, Ta, Ce, Ti, Mo, Sn, Y, etc.) can form strong electronic coupling with Pt and are often chosen as candidate supports for optimizing Pt-based catalysts in ORR. The Pt–MO x system can enhance the catalyst activity by driving electron transfer from Pt to MO x , thus increasing the Pt d energy band vacancies. , Meanwhile, the introduction of MO x provides resistance to degradation and agglomeration of the loaded Pt NPs, improving overall corrosion resistance of the catalyst in acidic environments. ,, However, the dense internal structure of MO x is not conducive to transport of catalytic species, often resulting in poor electrical conductivity. Moreover, conventional synthesis relying on simple blending cannot fully exploit the advantages of each component, making it difficult for Pt–MO x systems to achieve further performance breakthroughs. , Therefore, designing synthetic strategies that encompass 3D porous structures and improve electrical conductivity of Pt–MO x catalysts for efficient mass transport are crucial for the development of practical ORR catalysts.…”
mentioning
confidence: 99%
“…Previous research indicated that the metallic structure with more negative formation energy could exhibit more stable and greater leaching tolerance of M metal. , However, it remains a formidable challenge to contrallbly synthesize Pt-early transition metal intermetallics during the essential high-temperature annealing process as well as stabilize the NPs during the electrocatalytic process . Oxide coating is an effective and well-studied stategy to hinder the sintering and aggregation of NPs during the calcination procedure. , However, the removal of the inert coating template is complicated and time-consuming. Besides, the finally obtained carbon-supported metal/alloy features a weak metal–support interaction, which tends to have limted abilitiy to stabilize NPs during a long-term catalytic process. , Previous studies show oxide supports have a stronger interaction with a metal/alloy compared with the convential carbon support. This strong interaction resulting from charge transfer can effectively prevent the migration and coalescence of metal NPs. Additionally, it has been found that some metal oxides can also participate in catalyzing reaction process, thus pomotoing the transformation of intermediate products. More specifially, the oxyphilic oxides can trigger the CO conversion to improve the antipoisoning ability and reaction kinetics of Pt-based MOR catalysts by accelerating oxyhydryl formation. , These important and interesting findings motivate us to design high-performance catalysts by elaborately combining stable intermetallic compounds with functional oxides, which have rarely been reported.…”
mentioning
confidence: 99%